PERSEPSI KOMUNITAS PEMUDA TANI TERHADAP UPAYA BERKELOMPOKTANI DI BAHOROK - LANGKAT, SUMATERA UTARA - Dwi Febrimeli; Ameilia Zuliyanti Siregar; Ratna Gustin Luahambowo (AGRITEXTS: Journal of Agricultural Extension, 2020)
The low number of youth of farmers in the agricultural sector is one of the main problems in agriculture. The image of the agricultural sector that is less prestigious and less able to provide adequate compensation is the cause of the decline in the interest of young workers in the agricultural sector. Farmer regeneration can be implemented through the interest of youth in groups of farmers. which to develop creativity, productivity, innovation, empowerment, awareness, and independence. This study aims to determine the level of interest and factors that influence the interest of rural youth in groups in the Bahorok District, Langkat Regency, North of Sumatra Province. This study uses the method of explanatory saturation of samples with a quantitative approach, where as many as 37 of respondents (rural youth farmers). Data collection methods using observations, questionnaires and interviews. Data analysis uses a Likert scale and data processing uses multiple linear regression analysis. The results of the study concluded that the interpretation of the level of interest of rural youth in groups of 77.65% with a high category. Simultaneously farm income, family environment, community environment, social status and the role of extension workers simultaneously influence the interest of rural youth in farmer groups. Partially, farm income and family environment significantly influence the interests of youth while the family environment, social status and the role of extension workers do not affect the interests of rural youth in groups of farmers.